Foresight Study on the Adoption of Quantum Technology for Enhancing Supply Chain Efficiency in the Manufacturing Industry - Lim, Gou Qing; Salim, Siti Aisyah (Research in Management of Technology and Business, 2025)
Supply Chain Optimization (SCO) is key to making manufacturing more efficient, cost-effective , and sustainable. By leveraging advancements in Quantum Technology, including quantum computing, quantum sensing, and quantum communication, SCO can achieve new levels of innovation and transform how supply chains operate. Malaysia is still in the initial stages of adopting QT, hindered by challenges such as limited infrastructure, expertise and strategic foresight. This study identifies the issues, challenges and trends of QT adoption for supply chain optimization in the manufacturing sector, which evaluates high-impact and uncertainty factors, and develops future scenarios. A mixed-methods approach was utilized, which incorporating qualitative methodologies such as STEEPV (Social, Technological, Economic, Environmental, Political, and Values) and Impact-Uncertainty analysis, as well as quantitative methods using SPSS for statistical analysis. 384 questionnaires had been distributed with response rate 61.92%. Data collected from the respondent revealed critical factors such as technological advancement and government policy as the most impactful and uncertain. These insights informed the development of four future scenarios: Tech-Driven Growth, Policy Push Without Tech Readiness, Tech-Led Adoption Without Government Support, and Stagnant Growth. Each scenario provides strategic implications for navigating uncertainties in QT adoption. The study concludes with a discussion emphasizing the need for proactive policy-making, collaboration, and investment in technological capabilities to unlock QT's potential for supply chain optimization. This research offers a comprehensive framework for strategic planning and contributes to advancing Malaysia’s readiness for the integration of QT in manufacturing.